The Financial and Health Diaries: Using diaries to improve a health insurance program to better meet health needs in rural Nigeria - Kramer, Berber; Janssens, Wendy (PharmAccess Foundation, 2017)
How frequently do people get sick? What diseases do they get? How often do people seek care? And when seeking care, where do they go, and what do they spend? These and other questions were investigated in the Financial and Health Diaries study, consisting of weekly interviews with 240 households, over a one-year period. 120 of these households were located in Kwara State, Nigeria. The recorded data shed light on how to improve the insurance program in terms of provider network and quality of services within the Kwara State Health Insurance program.